Impact Assessment of FLDs on Paddy in North Eastern Himalayan Region (Indian Journal of Extension Education, 2017)
Rice is an important staple food for more than half of the global population. Krishi Vigyan Kendra Tawang, conducted demonstrations on paddy from 2011- 14 for improvement of paddy production in Tawang district of Arunachal pradesh. An impact evaluation was based on the comparison of participant and non-participant farmers with reference to increase in knowledge level and adoption of participant farmers of improved practices of paddy production. FLDs were carried out in a systematic manner on farmers fields to show the worth of HYV in comparison to local varieties and there by convincing farmers about potentialities of improved practices. The highest yield12 q/ ha was recorded in the year of 2011- 14 in the FLDs, which was 40 per cent more over the farmers practices. The gross returns (` 19200/ha) and net returns (`6200/ha) with higher cost benefit ratio 1.5:1 compared to 1.2: 1 of non-participant, FLDs programme to improve overall knowledge and adoption amongst the farmers in the region to boost paddy production.